The October list : a novel in reverse - Deaver, Jeffery (New York : Grand Central Publishing, 2013)
"Gabriela McKenzie's daughter has been kidnapped. In exchange for her safe return, her abductors demand two things: $400,000 in cash, and a document known only as the October List"--Provided by the publisher
Keywords: Kidnapping -- Fiction; Securities industry -- Corrupt practices -- Fiction; Women executives -- Fiction; Executives -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Suspense fiction; Mystery fiction